2014
DOI: 10.3109/10717544.2014.956849
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneously injected ivermectin-loaded mixed micelles: formulation, pharmacokinetics and local irritation study

Abstract: Clinical application of ivermectin (IVM) is limited by several unfavorable properties, induced by its insolubility in water. Slight differences in formulation may change the plasma pharmacokinetics and efficacy. In this study, an IVM-loaded Soy phosphatidylcholine-sodium deoxycholate mixed micelles (IVM-SPC-SDC-MMs) were developed to improve its aqueous solubility, aiming to make it more applicable for clinical use. First, IVM-SPC-SDC-MMs were prepared using the co-precipitation method. After formulation optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Hence, to overcome the problem of poor water solubility and obtain a stable injectable formulation of ivermectin, several commercial preparations have been developed which use organic solvents as vehicles. However, high concentrations of organic solvents have been reported to induce significant side effects in many species [26]. Frosch reported that pain and inflammation at the injection site were commonly observed side effects of commercial ivermectin preparations [27].…”
Section: Impact Of Ivermectin Formulations On Its Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, to overcome the problem of poor water solubility and obtain a stable injectable formulation of ivermectin, several commercial preparations have been developed which use organic solvents as vehicles. However, high concentrations of organic solvents have been reported to induce significant side effects in many species [26]. Frosch reported that pain and inflammation at the injection site were commonly observed side effects of commercial ivermectin preparations [27].…”
Section: Impact Of Ivermectin Formulations On Its Pharmacokineticsmentioning
confidence: 99%
“…In this study, oleic acid was found to be an efficient vehicle for ivermectin due to its ability to enhance the solubility and transport by reducing the p-glycoprotein (P-gp)-mediated efflux of ivermectin. The composition of various formulations of ivermectin and their characteristic features is described in Table-1 [7,26,28,32-61]. Vehicles, such as oils, liposomes, and other microparticles, can reduce drug metabolism and can enhance the release of large quantities of the active form of the drug over a long period of time to the target site by altering its pharmacokinetics [62].…”
Section: Impact Of Ivermectin Formulations On Its Pharmacokineticsmentioning
confidence: 99%
“…For example, albendazole is essentially insoluble in water, thus poorly absorbed through gastrointestinal tract. Similarly, IVM has a solubility of only 4 ug mL −1 in water and must be solubilized by surfactants and administrated in the form of micelles. Second, these drugs are typically limited by short circulation time.…”
Section: How Can Nanodelivery Systems Transform the Treatment Of Helmmentioning
confidence: 99%
“…Phosphatidylcholine (PC) and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine polyethylene glycol 2000 (DSPE PEG 2000; DP) have been widely used as pharmaceutical excipients because of their proven safety. [27][28][29][30][31] High concentrations of DP can solubilize drugs to a large extent. PC can adjust the hydrophobic segment aggregates to form a stable inner core to promote drug accommodation via hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%